Peran Pendamping Usaha Terhadap Resiliensi UMKM Melalui Legalitas Usaha Pasca Covid-19 - Sampurnawati, Sampurnawati; Dodik Jatmika; Ahmad Yamani; Mahyudiansyah, Mahyudiansyah (FKIP, Universitas Palangka Raya, 2025)
This study aims to analyze the role of business mentoring in shaping the resilience of Micro, Small, and Medium Enterprises (MSMEs) in South Kalimantan after the COVID-19 pandemic, with business legality serving as a moderating variable. The pandemic has tested the endurance of the informal sector, particularly MSMEs lacking formal legal status. Using a quantitative approach, data were collected from 250 MSME actors in South Kalimantan through questionnaires and analyzed using SmartPLS software. The findings indicate that business legality—such as ownership of a Business Identification Number (NIB) or Micro and Small Business License (IUMK), P-IRT/BPOM certification, Intellectual Property Rights (trademark), and halal certification—has a positive and significant effect on MSME resilience. These legal recognitions serve as gateways to accessing financial support, ensuring operational sustainability, and creating partnership opportunities, among others. This study recommends strengthening MSME legalization programs as a strategic effort to enhance local economic resilience, emphasizing the critical role of human resources who provide mentoring to build the capacity of MSME actors in South Kalimantan